Crystal structure of 1,3-dihydroxy-6,8-dimethoxy-2-(6-methyltetrahydro-2Hpyran-2-yl)-4a,9a-dihydroanthracene-9,10-dione, C22H22O7 - Shan Shu-jun; Cao Yao-yao; Yao Ping; Du Pei-pei; Chen Sai; Li Hong-lei (Zeitschrift für Kristallographie - New Crystal Structures)
C22H22O7, monoclinic, P21/n (no. 14), a = 7.8761(5) b = 17.0563(11) Å, c = 14.0504(10) Å, β = 95.563(4)°, V = 1878.6(2) Å3, Z = 4, Rgt(F) = 0.0504, wRref(F2) = 0.1475, T = 296(2) K.